Delivery of Prime editing in human stem cells using pseudoviral NanoScribes particles - Thibaut Halegua; Valérie Risson; Julien Carras; Martin Rouyer; Laurent Coudert; Arnaud Jacquier; Laurent Schaeffer; Théophile Ohlmann; Philippe Emmanuel Mangeot (Nature Communications)
Abstract Prime Editing can rewrite genes in living cells by allowing point mutations, deletions, or insertion of small DNA sequences with high precision. However, its safe and efficient delivery into human stem cells remains a technical challenge. In this report, we engineer Nanoscribes, virus-like particles that encapsidate ribonucleoprotein complexes of the Prime Editing system and allow their delivery into recipient cells. We identify key features that unlock the potential of Nanoscribes, including the use of multiple fusogens, the improvement of pegRNAs structures, their encoding by a Pol II system and the optimization of Prime-Editors. Nanoscribes edit HEK293T with an efficiency of 68% at the HEK3 locus with increased fidelity over DNA-transfection and support pegRNA-multiplexing. Importantly, Nanoscribes permit editing of myoblasts, hiPSCs and hiPSCs-derived hematopoietic stem cells with an editing efficiency up to 25%. Nanoscribes is an asset for development of next generation genome editing approaches using VLPs.